Performance Analysis of Large Intelligent Surface Enabled 6G Wireless Networks - Amgad, Mariam; Farrag, Sara; Maher, Engy A.; El-Mahdy, Ahmed (2023 2nd International Conference on Smart Cities 4.0, 2023)
Wireless communication has become a vital part of our lives. However, the increasing demand for high-speed and reliable wireless communication has created considerable obstacles to achieving these demands. The limited available bandwidth and the significant interference created by other wireless devices are considered major issues. To address these issues, large intelligent surfaces (LISs) have emerged as a promising solution to boost the communication network's performance. This paper analyzes the system's performance of a LIS-assisted network, where LIS is a sort of reconfigurable intelligent surface (RIS) distinguished by its high number of elements. Accordingly, the outage probability (OP), ergodic capacity (EC) and average bit error rate (BER) are derived. Numerical results show that as the value of the transmitted signal-to-noise ratio (SNR) increases the system's overall performance is enhanced. Moreover, increasing the number of LIS elements enhances the overall performance of the system. In addition, as the distance between the source and LIS increases the system's overall performance begins to decline.